Radiotherapy Treatment Plan Quality Metrics for Postmastectomy Breast Cancer Patients Using Conformal Planning Techniques - Garima Gaur; Raja Paramjeet Singh; Om Prakash Gurjar; Pardeep Garg; Romikant Grover; Manraj Singh Kang; Gurpreet Kaur; Sheetal Sheetal; Vinod Dangwal (Iranian Journal of Medical Physics, 2022)
Introduction: The purpose of this study is to evaluate and compare treatment plan quality metrics for postmastectomy breast cancer patients using 3-Dimensional conformal radiotherapy (3DCRT) and intensity-modulated radiotherapy (IMRT) planning techniques.Material and Methods: The current study included 50 postmastectomy breast cancer patients out of which 24 were planned with 3DCRT and 26 with IMRT technique. Treatment plan quality metrics, namely homogeneity index (HI), conformity index (CI), conformation number (CN), uniformity index (UI) and spillage index (R50), volume receiving 110% and 95% of the prescribed dose (V110% and V95%) were calculated and compared for the two planning techniques.Results: IMRT plans have better conformity, homogeneity indices, and lower V110% than 3DCRT plans with an almost similar R50% and V95%.Conclusion: Quantitative values of radiotherapy treatment plan quality metrics for the target are found in favour of the IMRT technique rather than 3DCRT. Implementation of these five parameters is helpful for evaluating treatment plans along with slice by slice and DVH analysis.